PREVALENCE OF FLUOROSIS AMONG SCHOOL CHILDREN AND CATTLE POPULATION OF HIRAKUD TOWN IN ORISSA - PRADHAN, KHAGESWAR; P. C. MISHRA (The Bioscan, 2006)
An epidemiological study was conducted on the prevalence of fluorosis in Hirakud town ,an industrial town of Western Orissa and the results were compared with two sub-urban and non- industrial towns located some 80 km away from Hirakud as control sites. Results revealed around 14-22% increase in teeth mottling (soiling) and aberration among school children in Hirakud over the control sites and 20-25% more in cattle population. Analysis of hospital records for out- patients although do not reveal any admission for treatment of fluorosis ,may be because of absence of specialists ,the admission rate with complain on teeth and bone related diseases has decline in Hirakud in comparison to the data of 2001-2002.Chi-square test indicates an association between prevalence of fluoride in environment and prevalence of fluorosis. Thus , the fluorosis has not affected the children as only teeth abrasions have been observed which might be due to other factors like health and hygiene. In Hirakud, the level of fluoride in water is within permissible limit, which may be a cause for no detectable dental or skeletal fluorosis among children excepting at the level of mild mottling or abrasion of teeth.It may be desirable to corroborate these findings with hematological studies.